Faux fun Diamond & stripe patterns everything you need to for painting patterned faux finishes (Long beach, CA Faux Fun, Inc., 2004)
This videodisc demonstrates how to paint different types, tyles and sizes of stripes and diamond patterns.
DVD
Presenter, Barbara Wurden.
Keywords: Decoration and ornament; Color decoration and ornament; Finishes and finishing; Interior walls -- Decoration; Interior decoration